Developmental Tasks of University Students: A Scholarly Examination of Evolving Patterns and Implications - Hamzah, Rifqy Muhammad; Merliana, Anggit; Irma Ari Irawan, Tb Moh (Indonesian Journal of Primary Education, 2024)
Each individual will go through a period of early adult development characterized by various types of life demands that are different from the previous stages. When entering early adulthood, individuals are required to explore careers, start   careers, invest in self-development, start family life and optimize life skills needed to achieve success. This study aims to describe the achievements of student development tasks in early adulthood which include aspects of religious life foundation, ethical behavior foundation, emotional foundation, intellectual foundation, responsibility awareness, social role as a man or woman, self-acceptance and development, economic behavioral independence, career insight and preparation, maturity of relationships with peers, and self-preparation for marriage and family life. The method used in research is quantitative descriptive with survey research design. Data collection is carried out with the Developmental Task Inventory (ITP) instrument which is then analyzed using a Development Task Analysis (ATP) application. The research sample consisted of 68 students. The results showed that the average level of developmental tasks was 6.71, which indicates the developmental level of individuality. From the results obtained, each aspect has a different level of development. However, these different levels do not mean that one level is better than the other. An overview   of the results of all aspects can be taken into consideration in evaluating and designing strategies to optimize student development.